The Influence Of Demonstration Methods On Skills Care Breast On Mother Nifas In Pbm (Practice Independent Midwife ) - Ulfa, Siti Maria; Wulandatika , Darmayanti; Suryati, Suryati (Sean Institute, 2022)
Introduction: Correct breastfeeding technique is one influencing factor for successful breastfeeding, with a target for the province of South Kalimantan of 80% of babies exclusive breastfeeding, correct breastfeeding technique _ is one _ influencing factor for successful breastfeeding. Study this aim for knowing the influence of method demonstration on Skills cares mother's breast childbirth. Method: Research this is pre-experimental research with a one-group pretest approach posttest design, and retrieval sample with a purposive sampling technique amounted to 30 mothers postpartum customized with criteria inclusion and exclusion. The instrument in a study is a checklist. The data analysis used is Wilcoxon. Result: Average skill score of the respondent before being given the demonstration is 6.17 meanwhile score of Skills respondents after being given the average demonstration is 14.63. Statistical test results bivariate obtained p value = 0.000 < α = 0.05. There is an influence of Demonstration Care Breast to Skills Care Breasts on Postpartum Mothers in the PBM work area. Discussion: Yes influence demonstration care breast to Skills care mother's breast childbirth. Need developed use of media, tools, and methods in as an effort to strengthen education health mother childbirth specifically about care breasts that can support breastfeeding success _ both through institutions education and giving service health.